EVALUATING THE ACCEPTABILITY AND FEASIBILITY OF PROJECT ACCEPT: AN INTERVENTION FOR YOUTH NEWLY DIAGNOSED WITH HIV - Hosek, Sybil G. (2011)
Given the potential for negative psychosocial and medical outcomes following an HIV diagnosis, Project ACCEPT, a 12-session behavioral intervention, was developed and pilot-tested for youth (aged 16–24) newly diagnosed with HIV. Fifty participants recently diagnosed with HIV were enrolled from 4 sites selected through the Adolescent Medicine Trials Network (ATN). The majority of participants identified as African American (78%). Feasibility and acceptability data demonstrated high rates of participation and high levels of satisfaction with the intervention program from both participants and staff. Exploratory outcome data demonstrated improved levels of HIV knowledge that were sustained over time (Cohen’s effect [d] d = .52) and improvements in peer (d = .35) and formal (d = .20) social support immediately postintervention. Gender differences emerged over time in the areas of depressive symptoms, family social support, self-efficacy for sexual discussion, and personalized stigma. Project ACCEPT appears to be an acceptable and feasible intervention to implement in clinical settings for youth newly diagnosed with HIV.